Stable salts of the hexacarbonyl chromium(I) cation and its pentacarbonyl-nitrosyl chromium(I) analogue - Jan Bohnenberger (Nature Portfolio, 2019)
Carbonyl complexes have been studied extensively thanks to their rich substitution and redox chemistry, but most homoleptic transition metal carbonyl complexes isolated in the condensed phase are neutral or anionic. Here, the authors isolate two homoleptic carbonyl radical cations in the condensed phase; both 17-electron [Cr(CO)6]•+ salts.